An Epidemiological Management Approach to Stroke Disease in Coastal Communities: A Structural Model for Tertiary Prevention - Robby, Krish Naufal Anugrah; Ma'rufi, Isa; Ouassou, El Houssin; Izzah, Latifatul (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: Stroke survivors in coastal areas face major challenges, such as limited access to health services, minimal post-stroke education, and inadequate monitoring. Without a targeted tertiary prevention strategy, the risk of recurrence and disability remains high. This study aimed to develop a stroke management model to enhance self-control and support community-based health policy planning.Methods: A cross-sectional study was conducted among 45 stroke survivors in the Puger Subdistrict, Jember Regency, using a total sampling approach. Data were collected through questionnaires and measurements of blood pressure, cholesterol, and random blood glucose using touch-based devices and digital sphygmomanometers. Path analysis was performed using Partial Least Squares structural equation modeling.Results: Clinical needs, such as elevated blood pressure and cholesterol levels, encouraged survivors to be more active in managing their conditions and increased their interactions with health services. However, paradoxically, poor self-management, such as infrequent blood pressure monitoring and unhealthy diets, places a greater burden on the health system. This indicates that an increased system response alone is insufficient without strengthening the individual roles. Family history and blood glucose levels also contribute to indirect pathways. Conclusion: Preventing stroke recurrence requires a comprehensive epidemiological management approach, including clinical control, dietary education, and sustainable, community-based interventions. This model can serve as a basis for designing health programs and policies that are more responsive to the needs of coastal communities in the future.